성교육 자료 평가도구 개발과 적용 - 양순옥; 정금희; Yang Soon-Ok; Jeong Geum-Hee (Adong Kanho Hakhoe chi, 2003)
Purpose: This study was done to develop a reliable and appropriate evaluation tool for sexual educational materials and to apply it to video materials for recommendation of excellent materials. Method: The items of the content for evaluation were based on the previous studies on the sexual education and evaluation tools. After testing validity and reliability of tool, final evaluation tool for sexual educational materials was developed. The evaluation tool was applied to 84 video materials and the excellent materials were recommended. Result: The final evaluation tool for sexual educational materials which consisted of two parts was developed. One is the evaluation of basic information which includes 8 items: target population, type of materials, producer, year of production, subject, theme, running time, and guide book. The other is the evaluation of content which includes 36 items related to characteristics of material, purpose, efficiency and scope of content. After applying the tool to 84 video materials, 39 excellent sexual education materials were suggested. Conclusion: The systematic development of materials for sexual education appropriate to the specific subjects should be done. Producers should describe the basic information on the outside of materials. For recommending the excellent materials, the periodical standardized evaluation of sexual educational materials should be done, and the database of the excellent materials should be provided for further utilization.